Adenosine and Hemodialysis in Humans. (1st January 2001) - Guieu, Régis; Brunet, Philippe; Sampol, Jérome; Bechis, Guy; Fenouillet, E.; Mege, J.L.; Capo, C.; Vitte, J.; Ibrahim, Z.; Carrega, L.; Lerda, D.; Rochat, Hervé; et al.
Abstract: Background: Infections and hypotension are serious complications that develop during hemodialysis (HD) treatment. Adenosine (ADO), a strong hypotensive and immunosuppressive agent, may participate in these two HD complications, because high concentrations of ADO metabolites are found in dialyzed human plasma. ADO, which is released by endothelial cells, is quickly transformed into inosine (INO) by plasmatic ADO deaminase (ADA) and mononuclear cell ADO deaminase (MCADA). In plasma, the degradation of ADO into INO and its uptake by red blood cells (RBC) are both very rapid, resulting in the short half-life of ADO in blood. Methods: Using liquid chromatography, we evaluated ADO and INO plasma concentrations before and after HD session. Results: Before the HD session, ADO and INO plasma concentrations were higher in hemodialyzed patients than in controls and in peritoneally dialyzed patients. At the end of the HD session, ADO plasma concentration was increased. ADO plasma concentration for the undialyzed patients was in the same range as that of the controls. Before HD, ADA activity was higher in hemodialyzed patients (559±349 IU) than in controls (219±48 IU), and the activity rose during the session (665±135 IU). ADA activity in the undialyzed patients (222±80 IU) was in the same range as that of the controls (219±48 IU). Before the HD session, the MCADA activity (247±144 IU) was lower than in controls (624±99 IU). HD did not modify ADO RBC uptake. ADO inhibited mononuclear cell proliferation and interferon-γ production in humans. Finally, as much as 50 μM INO does not inhibit ADO uptake by RBC and does not modify ADA and MCADA activities. Conclusions: These data indicate that chronic HD inhibited MCADA activity and increased ADO plasma concentration. Both high ADO plasma concentration and low MCADA activity may be involved in dialysis-induced immune system failure and thereby favor infectious diseases.